Macroeconomic Determinants of Bilateral Trade: Evidence from India and Nepal - Adhikari, Padma Kumar (Journal of Management, 2024)
This study investigates the macroeconomic determinants of bilateral trade between Nepal and India using the Auto-Regressive Distributed Lag (ARDL) model to analyze both short-term and long-term dynamics. The analysis reveals that the GDP of both Nepal and India significantly impacts Nepal's exports, emphasizing the critical role of economic growth in enhancing trade. Financial development and Foreign Direct Investment (FDI) are also found to positively influence Nepal's export performance, highlighting the importance of a robust financial sector and foreign investment. Conversely, Nepal's GDP hurts imports from India, indicating a shift towards domestic production as the economy grows, while India's GDP positively influences Nepalese imports. Financial development further facilitates imports, underscoring the significance of financial infrastructure. Although Indian lending interest rates and FDI inflows showed varied significance, their directional impacts align with theoretical expectations. The study also confirms the stability of the ARDL model through diagnostic tests, reinforcing the reliability of the results. These findings provide critical insights for policymakers aiming to bolster trade relations between Nepal and India, emphasizing the need for macroeconomic stability, financial development, and targeted FDI policies to foster economic growth and regional integration.